Improving the conception rate of dairy cows by using a melatonin implant - Yildiz, A. (Sivar-Soc Italiana Veterinari Animali Reddito, 2015)
Introduction - Oxidative stress and maternal low blood progesterone levels during early embryonic development are a major cause of decreased pregnancy rate in dairy cows. It may be feasible to increase the conception rates by administering an appropriate antioxidant that stimulates the progesterone secretion and that prevents the effects of oxidative stress during early embryonic development in cows. Studies have demonstrated that melatonin may promote or contribute to the secretion of progesterone and has a powerful antioxidant effect. Therefore, the pregnancy rate in dairy cows could be improved through a melatonin treatment. Aim - The present investigation was undertaken to evaluate the effect of a melatonin implant on day 7 after AI on pregnancy rate in Holstein cows. Moreover, the effect of melatonin on progesterone levels and the anti-oxidant effect of melatonin was investigated. Materials and methods - A total number of 54 Holstein cows allocating 27 animals in each group were randomly assigned to one of two groups; trial (T) and control (C). Their estrous cycles were synchronized by two intramuscular injections of cloprostenol (an analogue of prostaglandin F-2 alpha) eleven days apart. Estrous exhibiting cows were artificially inseminated. Six implants/animal, each containing 18 mg of melatonin (Regulin, CEVA Turkey), were placed subcutaneously behind the ears of the cows in group T on day 7 after AI, while group C received no melatonin implants. From each group nine animals were chosen, from which blood samples were collected to determine erythrocyte glutathione peroxidase (GSH-Px) and superoxide dismutase (SOD) levels as well as plasma progesterone concentration just before implant insertion and on day 7 after implant insertion. Pregnancy diagnosis was carried out on day 60 post insemination through rectal examination. Results and discussion - The conception rate at first insemination was 55.6% and 29.6% for group T and group C, respectively. There was a tendency to have a higher conception rate for group T than group C. It was observed that the GSP-Px, SOD and plasma progesterone levels on day 7 after melatonin implantation increased significantly. Conclusions - The implanted melatonin on day 7 post insemination was found to enhance proportionally the conception rate in Holstein cows. This effect is probably due to the powerful antioxidant effect of melatonin and the increased concentrations of plasma progesterone in the melatonin treated cows.
Keywords: Pregnancy; melatonin; progesterone; antioxidant enzymes; dairy cows